Bibliometric analysis of global research on the clinical applications of aminoglycoside antibiotics: improving efficacy and decreasing risk - Zhao, Tengxiang; Chen, Nan; Zhang, Mingyue; Lin, Likai; Lin, Bin; Fang, Yuan; Hua, Zhihui; Liang, Chenyu (Frontiers in Microbiology, 2025)
BackgroundInfections by drug-resistant bacteria are a significant threat to human health worldwide although many drug-resistant bacteria are sensitive to aminoglycosides (AGs), an older class of antibiotics. AGs have played a significant role in clinical practice in recent years.MethodsPublications from 1 January 2013 to 31 December 2023 that described clinical research of AGs were identified by searching the Web of Science Core Collection Database. Visual presentations of different bibliometric networks were prepared using VOSviewer and CiteSpace.ResultsThere were 915 eligible publications and the annual number of publications increased over time. The United States had the most publications and was at the core of the cooperative network. Italy and Belgium had the highest quality publications, and many of the institutions with high yield and high research quality were in Australia. JA Roberts (University of Queensland, Australia) was the most productive author and was the author of many high-quality studies in cooperation with various other researchers. The majority of publications were in journals that focused on antibacterials, chemotherapy, and pharmacokinetics. Analysis of the most highly cited publications, references, and keywords, indicated that this research mainly focused on infections by drug-resistant bacteria, drug administration in vulnerable populations, safety, pharmacokinetics, combination therapy, and new methods of administration.ConclusionAGs have an increasingly important role in the treatment of infections by multidrug-resistant bacteria. Therapeutic drug monitoring should be performed in vulnerable populations, such as the elderly, children, and infants, to improve efficacy and reduce toxicity. Avoiding prolonged dosing cycles and refraining from using AGs in patients with the m.1555 A > G gene variant can significantly mitigate the risk of ototoxicity. Future studies should examine the pharmacokinetic and pharmacodynamic targets of AGs and assess the efficacy and safety of administration by inhalation to improve efficacy and decrease risk.